A review on up-cycle plastic waste material: current body of literature, knowledge gaps furniture design base from designer perception and user response / Fahmi Ahmad ... [et al.] - Ahmad, Fahmi; Ahmad, Mohammad Azroll; Saharudin, Haszlin; Khairi, Hanif Khairi (Universiti Teknologi MARA, 2018)
Understanding the characteristic design should be an emotion's role in various aspect of design, not only represent the goal of this research, but also the successfulness of any design that have good characteristic will success in the market. Some scholar has regarded the design characteristic as a main tool that all designer use and understand to deliver the product message and feeling that connect to the user feeling and emotion. This research project will propose the design and prototyping from up-cycle material to create furniture design in order to investigate from designers and the user response in developing design characteristic into the new upcycle furniture design. The wastes from the manufacturing process are harm to our health and environments and the pollution become a big major issue in Malaysia. However, by upcycling the materials or products to create another creative object could reduce the pollution issue and in the same time support the awareness sustainability campaign. This research will focus on user oriented in order to identify the use of upcycle material can play a role developing solutions for interesting and interactive furniture design by inserted the good characteristic in it. The motivation needs of user are often not researched, addressed, and misunderstand in developing the design idea. Therefore, an underlying objective of this research understudy is to investigate and develop design characteristic which illicit favorable responses from designer and user's opinion in their response and experience. The responses in the form of perceptions, opinions and those aspects resulting from in-depth observations of furniture design that derive from up-cycle material will be researched in this study. This is to understand the needs of designer and users and to contribute guidelines for the future development of up-cycle furniture design.